Expression of a Fusarium oxysporum endoglucanase in kluyveromyces lactis - Moukit, Farid; Amid, Azura; Mohd. Salleh, Hamzah (2011)
Cellulose is the main component in plant cell wall and thus the most abundant biopolymer on earth. Endoglucanase is one of the key constituent of a complex multi-enzyme system collectively known as cellulase which degrades cellulose into glucose. Cellulase has been used in various industries such as textile, detergent, food and feed, pulp and paper, and recently in bio-fuel industries. This research intends to clone and characterize functional endoglucanase enzyme from a thermophilic pathogenic plant fungus, Fusarium oxysporum, in suitable eukaryotic expression system (Kluyveromyces lactis). Kluyveromyces lactis have many advantages of higher eukaryotic expression systems such as: protein processing, protein folding, and post-translational modification. While being as easy to manipulate as ‘E. coli’, they give higher expression levels. This research will also optimize the process conditions required for the maximal formation of functional recombinant endoglucanase, followed by purification of the recombinant enzyme before determining the characteristics of the recombinant endoglucanase such as stability (pH, temperature) and activity (substrates, effectors and inhibitors).